Hybrid machine learning algorithms to predict condensate viscosity in the near wellbore regions of gas condensate reservoirs - Behesht Abad Abouzar Rajabi; Mousavi Seyedmohammadvahid M.; Mohamadian N. Nima; Wood D. А. David; Ghorbani Hamzeh; Davoodi Sh. Shadfar; Ahmadi A. M. Alvar Mehdi; Shahbazi Kh. Khalil (2021, 2021)
Title screen